Assessing the impact of information technology on enterprise level performance - Kevin Crowston; Treacy, Michael E. (Proceedings of the Sixth International Conference on Information Systems (ICIS), 1986)
Implicit in most of what we do in MIS is the belief that information technology (IT) has an impact on the bottom line of the business. Surprisingly, we rarely know if this is true. It is very difficult to trace and measure the effects of information technology through a web of intermediate impacts upon enterprise level performance. In this paper, we review research that has been performed on enterprise level impacts of information systems, with a particular emphasis on research that has attempted to measure those impacts. We begin with a survey of articles published within the last ten years. This is followed by a discussion of the reference disciplines that underlie most of this work. From this we are able to draw conclusions about future directions for research in this area.
Keywords: Information Technology; Organization